Implementation of antibiotic use guidelines for fresh traumatic wound at Siriraj Hospital - Rujipas Sirijatuphat (2018)
© 2015, Medical Association of Thailand. All rights reserved. To determine the effectiveness of implementing a clinical practice guideline (CPG) on antibiotic use for adults with fresh traumatic wounds who attended the trauma center at Siriraj Hospital, Bangkok. Material and Method: A prospective study of 600 adult patients who had fresh traumatic wounds (≤6 hours) was conducted at Siriraj Trauma Center from March 2013 to March 2014. The CPG was introduced to physicians, nurses and medical students by posting the CPG at the patient care areas of the trauma center. The outcomes were an appropriate classification of wounds according to the CPG recommendations, prevalence of antibiotic prescribing, incidence of wound infection and compliance with the CPG. Results: Clean-contaminated wounds that did not need antibiotic treatment and clean-contaminated and contaminated wounds that required antibiotics were observed in 63.2, 6.7, and 30.1% of the patients, respectively. Antibiotics were given to 512 patients (85.3%). Infections occurred in six patients (1.0%). Antibiotic prescription according to CPG recommendations was observed for 243 patients (40.5%). The prevalence of antibiotic use in the CPG-compliant group (65.8%) was significantly less than that in the CPG-noncompliant group (98.6%) (p<0.001). The patients in the CPG-compliant group had more contaminated wounds than those in the CPG-noncompliant group (51.4 vs. 15.7%, p<0.001). The incidences of wound infection were very low in both groups and not significantly different (1.2 vs. 0.8%, p = 0.690). Conclusion: Antibiotic prophylaxis was necessary in less than 36.8% of adults with fresh traumatic wounds who attended Siriraj Trauma Center. Compliance to CPG implementation using simple intervention seemed to be low. Adhering to CPG recommendations for antibiotic prophylaxis in adults with fresh traumatic wounds can reduce the unnecessary prescribing of antibiotics without increasing the rate of wound infection.